Intestinal parasites and enteropathogenic bacteria in school age children of Maracaibo, Venezuela - Liliana Patricia Gómez-Gamboa; Vannessa Velasco; Jessica Villasmil; Messaria María Ginestre-Perez; José Bermudez-Gonzalez; Armindo José Perozo Mena; Zulbey Rodríguez (Kasmera, 2018)
Intestinal pathogens infection represents a global public health problem, and are associated with morbidity and mortality high rates, particularly in children; we determined the relative frequency of intestinal parasites and diarrheagenic bacteria in 22 children of the Basic State School "Comandante Remigio Negron", Maracaibo, Venezuela. Most of the children showed elevated parasites (72.73%) and polyparasitism (22.73%). The highest frequency corresponded to the protozoa and chromist (95.65%), finding a high frequency of Blastocystis sp. (52.17%); while Giardia intestinalis was detected only in 8.70%, in contrast to global data that indicate it is the most frequent protozoan species in children. In addition, the complex E. histolytica/E. dispar / E. moshkovskii (13.04%) was detected and also Hymenolepis nana (4.35%). Non-typhoidal Salmonella (4.54%) was also detected, the most common bacterial pathogen causing foodborne infection globally and the main stool-isolated bacteria in pediatric patients of the region. These results demonstrate the high relative frequency of intestinal parasites in the studied children, with predominance of protozoa and chromist, as well as the presence of Salmonella sp.; highlighting the need to promote the hygiene and environmental sanitation, to reduce the relative frequency of intestinal pathogens and their consequences to health and school performance.